Low-skilled, low socio-economic, young, co-resident, working fathers : their experience of fatherhood : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Turitea, Palmerston North, New Zealand - Rouch, Gareth (Massey University, 2009)
Low-skilled, low socio-economic status, young, co-resident, working fathers: Their experience of fatherhood Using open-ended interview techniques, 23 low-skilled, low socio-economic status fathers aged 20-29 were interviewed about their experience of fatherhood. All participants were in unskilled jobs and all lived with and supported their partners and child/children. This population of fathers is generally overlooked by researchers. Because they take responsibility for some of society’s most vulnerable families and children, understanding how they conceive of their role as fathers can promote the welfare of those families and children. Participants were recruited by casual connections, snowballing and advertisement. The interviews explored the participants' experience of fatherhood and their reasons for being active and committed family members. Focus was given to how they made sense of fatherhood in terms of their life course. Participants had two interviews, the first generic and the second idiographic. Interviews were tape-recorded and later transcribed. A social constructionist approach was used: transcripts were analysed by identifying and examining the primary domains in which participants experienced fatherhood. Participants spoke of fatherhood as an affective activity, the primary object of good fatherhood being to maintain an emotional bond with one’s children. Being a good father was thought to involve eschewing deleterious family practices such as those which had marred their own childhoods. In this regard, participants saw themselves as repairing their family-of-origin's dysfunctional style. Providing was described as a core feature of fatherhood – subsidiary to, but corollary on, being an emotionally-engaged father. Good fathers were described as committed providers, albeit participants did not consider their own limited earning capacity to compromise their fatherhood. Obtaining a job and providing for one’s family was one of the ‘pro-socializing’ effects of fatherhood. Participants considered fatherhood to not only improve but to also redeem their lives, giving a purpose and focus they had lacked prior to their becoming parents. Being a good father also involved being a good partner. For many of the participants, this involved adopting non-gendered roles in the home. The sharing of housework and childcare improved home life by reducing the partner's workload. Those who failed to adopt the gender-neutral stance acknowledged this as a personal shortcoming that they planned to remedy. Fatherhood for these 23 interviewees was one of the few means by which they could obtain social value and status as adults. They lacked access to financial resources, education or supportive family connections, but fatherhood was a domain in which they could present themselves as significant members of society. It also provided a network of emotional relationships which promoted their sense of self-worth and their social and emotional wellbeing.
Keywords: Fatherhood; Fathers; Low socio-economic status; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380105 Social and community psychology